2022
DOI: 10.1021/acs.inorgchem.2c03043
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Engineering in Na2MSn2(NCN)6 (M = Mn, Fe, Co, and Ni) Based on Electronic Structure Theory

Abstract: Quaternary transition metal cyanamides Na2MSn2(NCN)6 with M = Mn, Fe, Co, and Ni were prepared via solid-state metathesis reactions between Na2Sn(NCN)3 and binary transition metal fluorides MF2 in a 2:1 molar ratio. All phases crystallize isotypically in [NiAs]-derived structures (P3̅1m) with inter- and intra-layer cation ordering over the octahedral sites. This leads to a highly asymmetric coordination of the NCN2– anion, resulting in a strong degree of cyanamide character, which is confirmed via IR measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Besides binary C 3 N 4 , carbon–nitrogen-based complex anions such as carbodiimide NCN 2– , guanidinate , CN 3 5– , or ortho-nitrido carbonate CN 4 8– also allow to generate three-dimensional materials in combination with (transition) metal cations, and these may be regarded as complex salts offering rich structural diversity and physicochemical properties. Molecular melamine, C 3 H 6 N 6 , the trimer of molecular cyanamide, H 2 NCN, plays a special role not only because it may be used for making g-C 3 N 4 (see above) but also due to the fact that it allows for deprotonation to prepare metal melaminate salts, yet another way to arrive at high-performance photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Besides binary C 3 N 4 , carbon–nitrogen-based complex anions such as carbodiimide NCN 2– , guanidinate , CN 3 5– , or ortho-nitrido carbonate CN 4 8– also allow to generate three-dimensional materials in combination with (transition) metal cations, and these may be regarded as complex salts offering rich structural diversity and physicochemical properties. Molecular melamine, C 3 H 6 N 6 , the trimer of molecular cyanamide, H 2 NCN, plays a special role not only because it may be used for making g-C 3 N 4 (see above) but also due to the fact that it allows for deprotonation to prepare metal melaminate salts, yet another way to arrive at high-performance photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…15 A FT-IR spectrum of the sample displays two absorption bands: asymmetric stretching (ν as 1960 cm −1 ) and deformation (δ 681 cm −1 ) vibrations of NCN 2− (Figure S1b). 28,29 Judging from the absence of a symmetric stretching vibration (approximately 1250 cm −1 ), which is IR-forbidden for 24,25,30,31 UV−vis DRS revealed that the absorption edge of the obtained La 2 O 2 NCN exists at around 260 nm (Figure S1c). This value of the absorption edge position is comparable to that reported in a preceding paper by another group.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Moreover, systematic Ni substitution into this NiAs-derived structure type led to a pronounced increase in the current density, maximized in Co 0.9 Ni 0.1 NCN. In a similar manner varying the nature of the transition-metal species in Na 2 M Sn 2 (NCN) 6 ( M = Mn, Fe, Co and Ni) quaternaries, which also all crystallize isostructurally in NiAs-derived structures, has been shown as to be an efficient means of band gap tuning …”
Section: Applicationsmentioning
confidence: 99%
“…In a similar manner varying the nature of the transition-metal species in Na 2 MSn 2 (NCN) 6 (M = Mn, Fe, Co and Ni) quaternaries, which also all crystallize isostructurally in NiAs-derived structures, has been shown as to be an efficient means of band gap tuning. 60 Meanwhile MnNCN has been successfully integrated as an electrocatalyst for CuWO 4 photoanodes increasing the photocurrent by a stunning 30% in a phosphate electrolyte. 146 Furthermore, in-depth structural analysis revealed that MnNCN is activated in situ to form a MnNCN@MnPO x core−shell structure thereby mimicking a manganese phosphate electrocatalyst and highlighting the importance of surface chemistry.…”
Section: Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation